Liberty as progression: a study of the revolutions idealized in Areopagitica, The marriage of heaven and hell, and The matrix - Rocha, Adalberto Teixeira de Andrade (Em Tese, 2008)
I address the assumptions of Areopagitica, The Marriage of Heaven and Hell and The Matrix as well as provoke their ideals in order to expose the status of their liberty and progression towards truth as one that is in no sense absolute, but time and space specific.